High-interfacial-activity in-situ self-assembly tough cement-based pavement material and preparation method thereof
By introducing high-interface active hydrogel accelerator into hydrogel-cement materials, the reaction between cement hydration products and hydrogel surface is enhanced, and the problem of weak interface bonding force of traditional materials is solved, thereby achieving the extension of material life and the reduction of maintenance costs.
Patent Information
- Application Number
- CN202411616729.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The hydrogel and cement interface bonding force of traditional hydrogel-cement materials is weak, resulting in short material life, frequent maintenance, and high maintenance costs, which limits its promotion and application in pavement materials.
By introducing high-interface active hydrogel promoters, the high-reactive amino groups and silicon-aluminum ions are used to promote the reaction of cement hydration products with the hydrogel surface, and generate hydration products with high stability and strength, enhancing the binding force between the hydrogel and cement interface.
It significantly improves the interface bonding between hydrogel and cement matrix, extends the service life of the road surface materials, reduces maintenance costs, and meets the environmentally friendly and low-carbon urban construction requirements.
Smart Images

Figure CN119707386A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high-interfacial-activity in-situ self-assembly tough cement-based pavement material and a preparation method thereof, belonging to the technical field of cement-based pavement materials. Background Art
[0002] In order to advocate national fitness and sports for all, many places have built a large number of sports parks, fitness trails and other places for people to exercise and exercise daily. In order to improve the comfort of walking on pedestrian walkways, buffer impact force and reduce joint injuries, the pavement materials used in parks and public fitness venues are mostly elastic materials. Flexible asphalt pavement materials are widely used in pavement paving in parks and public fitness venues due to their high flexibility and good pedestrian comfort. However, with the development of society and the improvement of environmental protection requirements in urban construction, the shortcomings of flexible asphalt pavement materials have gradually become prominent. They mainly include poor aging resistance, high temperature paving during construction to generate a large amount of carbon emissions, and the generation of polluting gases and dust during construction, which do not meet the concept of sustainable development of modern cities and the development requirements of environmental protection in urban construction.
[0003] Hydrogel-cement composite materials have the advantages of high toughness, low construction technology requirements, and green construction process, and have certain compressive strength. However, traditional hydrogel-cement materials have obvious problems of weak interfacial bonding between hydrogel and cement. This is because the bonding between traditional hydrogel and cement matrix relies on the hydration products formed by cement components on the surface of hydrogel, but because the hydration products contain a large amount of calcium hydroxide, which lacks stability and has low strength, the bonding force at the cement-hydrogel interface is relatively weak. When subjected to impact loads, it is very easy to cause interfacial peeling between hydrogel and cement, which leads to structural damage. Therefore, when using traditional hydrogel-cement composite materials to make pavements, there are shortcomings such as short life, frequent maintenance, and high maintenance costs, which limit the promotion and application of this material. Summary of the invention
[0004] Purpose of the invention: The first purpose of the present invention is to provide a high-interfacial activity in-situ self-assembled tough cement-based pavement material. The second purpose of the present invention is to provide a method for preparing such a high-interfacial activity in-situ self-assembled tough cement-based pavement material. After the high-interfacial activity hydrogel is compounded with the cement-based material, it can effectively consume the calcium hydroxide produced by cement hydration, greatly enhance the interfacial bonding force between the hydrogel and the cement matrix, and improve the service life of the prepared pavement material.
[0005] Technical solution: The high-interfacial-activity in-situ self-assembled tough cement-based pavement material of the present invention is characterized in that the pavement material comprises the following raw materials in parts by weight: 20 to 60 parts of a cementitious material containing silicate cement, 0.2 to 0.5 parts of a hydrogel accelerator, and 1 to 7 parts of a hydrogel initiating solution, wherein the hydrogel initiating solution comprises 1 to 5 parts of poly-N-isopropylacrylamide, 0.3 to 1.5 parts of sodium acrylate, 0.03 to 0.12 parts of a cross-linking agent, 0.03 to 0.12 parts of an initiator, and 20 to 60 parts of water; the chemical structural formula of the hydrogel accelerator is shown in formula (1):
[0006]
[0007] Furthermore, the preparation method of the hydrogel accelerator comprises the following steps:
[0008] (1) placing tetramethylenediamine (TEMED) in an alkaline solution for surface treatment, adjusting to neutrality, adding a silane coupling agent, and heating for reaction to obtain a system containing an intermediate (TK);
[0009] (2) Adding lithium aluminosilicate (LiAlSiO 4 ), and heated to react to obtain a hydrogel promoter (TL).
[0010] Furthermore, in step (1), the alkaline solution includes at least one of a sodium hydroxide solution, a potassium hydroxide solution, and the like.
[0011] Furthermore, in step (1), the concentration of the alkali solution is 0.03 to 0.25 mol / L.
[0012] Furthermore, in step (1), the alkaline solution is sufficient to completely immerse the TEMED, and the alkaline solution is used to increase the reactive sites on the surface of the TEMED.
[0013] Furthermore, in step (1), an acidic substance is used to adjust to neutrality, and the acidic substance includes at least one of nitric acid, sulfuric acid, etc.
[0014] Furthermore, in step (1), the silane coupling agent includes γ-methacryloxypropyltrimethoxysilane (KH-570) and the like.
[0015] Furthermore, in step (1), the mass ratio of tetramethylenediamine to silane coupling agent is 0.1-0.3:0.03-0.08.
[0016] Furthermore, in step (1), the temperature of the heating reaction is 40 to 80°C, and the heating reaction time is 0.5 to 3.5 hours. Preferably, continuous stirring is performed during the reaction. In this process, the siloxane of the silane coupling agent (taking KH-570 as an example) forms a highly active complex containing silanol groups with water and the amino-alkyl groups on the surface of TEMED for subsequent Li + The grafting reaction process is shown in formula (2):
[0017]
[0018] Furthermore, in step (1), continuous stirring is performed during the reaction.
[0019] Furthermore, in step (2), the mass ratio of tetramethylenediamine to lithium aluminosilicate is 0.1-0.3:0.08-0.2.
[0020] Furthermore, in step (2), the temperature of the heating reaction is 50 to 95°C, and the heating reaction time is 1.5 to 5.5 hours. Preferably, continuous stirring is performed during the reaction. 4 Provided by Al 3+ , Li + The grafting is achieved by forming a coordination bond with the exposed silanol group on the intermediate (TK). The reaction process is shown in formula (3):
[0021]
[0022] Furthermore, in step (2), continuous stirring is performed during the reaction.
[0023] Furthermore, the cementitious material containing silicate cement includes at least one of ordinary silicate cement, PI silicate cement, PI silicate cement, slag silicate cement or sulfate-resistant silicate cement.
[0024] Furthermore, the initiator includes at least one of potassium persulfate, ammonium persulfate, sodium persulfate, etc.
[0025] Furthermore, the cross-linking agent includes at least one of N,N-methylenebisacrylamide, N,N'-methylenebisacrylamide and the like.
[0026] The method for preparing the in-situ self-assembled tough cement-based pavement material with high interfacial activity of the present invention comprises the following steps: adding a cementitious material containing silicate cement and a hydrogel initiating solution into a hydrogel accelerator and mixing them evenly to obtain the material.
[0027] Furthermore, when using the high-interface-activity in-situ self-assembled strong-tough cement-based pavement material, the high-interface-activity in-situ self-assembled strong-tough cement-based pavement material is formed into a pavement and then waited for solidification and hardening.
[0028] The present invention provides a high-interfacial-activity in-situ self-assembled tough cement-based pavement material and a preparation method thereof. After the high-interfacial-activity hydrogel is compounded with the cement-based material, the calcium hydroxide produced by cement hydration can be effectively consumed, thereby greatly enhancing the interfacial bonding force between the hydrogel and the cement matrix and improving the service life of the prepared pavement material.
[0029] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0030] The present invention firstly prepares tetramethylenediamine containing aluminosilicate as a hydrogel accelerator, and utilizes the highly active amino groups contained in tetramethylenediamine in the accelerator to realize LiAlSiO 4 Grafting, thereby more accurately strengthening the interfacial bonding between hydrogel and cement, overcoming the disadvantage of weak bonding between traditional hydrogel and cement matrix. When the hydrogel promoter is used to mix the hydrogel and cement together to form a highly interfacially active hydrogel-cement flexible composite material, the calcium ions released by cement hydration are combined with the silicon and aluminum ions on the surface of the hydrogel by utilizing the characteristics of active silicon and aluminum ions on the surface of the high-activity hydrogel to generate CSH gel and calcium aluminate (AFt), thereby forming a large amount of stable and high-strength hydration products at the interface between cement and hydrogel, while consuming the low-strength hydration product calcium hydroxide, greatly enhancing the interfacial bonding, and then improving the impact absorption percentage of the material surface, with extremely high service life, and no need for later maintenance. At the same time, lithium ions have a small ionic radius, high charge density, interaction with cement hydration products, and possible catalytic effects, so the Li ions on the hydrogel promoter can reduce the C in cement. 3 The electric potential barrier on the S surface promotes the interaction between water molecules and C 3 The combination of S accelerates C 3 The hydration process of S generates more CSH gel and Ca(OH) 2 , thereby promoting the rapid improvement of the strength at the organic-inorganic interface, matching the high reaction rate of cement hydration reaction with the rapid gelation of hydrogel, and forming a composite material with stronger interface bonding force. The present invention introduces hydrogel into cement-based pavement materials, which has many advantages over existing asphalt or organic pavement materials, such as green, low-carbon, environmentally friendly, and low comprehensive cost, and the new pavement material formed meets the standard requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the infrared spectrum of the hydrogel accelerator prepared in Example 1;
[0032] Figure 2 This is a sample of a highly interfacially active in-situ self-assembled tough cement-based pavement material prepared in Example 1;
[0033] Figure 3 This is a scanning electron microscope image of a sample of a highly interfacially active in-situ self-assembled tough cement-based pavement material prepared in Example 1. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0035] These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers.
[0036] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If there are no special instructions, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. Now, the technical solution of the present invention is further described in conjunction with the accompanying drawings and specific embodiments of the specification.
[0037] Example 1
[0038] 1. Preparation of hydrogel accelerator
[0039] (1) The tetramethylenediamine is completely placed in a 0.15 mol / L sodium hydroxide solution for surface treatment for 16 hours. After completion, the system is adjusted to neutrality with 0.1 mol / L nitric acid, and then a 3% by mass silane coupling agent (KH-570) aqueous solution is added according to a mass ratio of 0.3:0.03 of the tetramethylenediamine to the silane coupling agent, and then heated to 60° C. and continuously stirred at a speed of 200 r / min for 1.5 hours at this temperature. After completion, a system containing the intermediate (TK) is obtained and is set aside;
[0040] (2) Adding lithium aluminosilicate (LiAlSiO 4 ), the mass ratio of the two is 0.2:0.18. Then it is heated to 70℃ and stirred continuously at 500r / min for 3h at this temperature. After completion, the hydrogel promoter (TL) is obtained.
[0041] The obtained hydrogel promoter was subjected to infrared spectroscopy analysis, and its infrared spectrum is shown in Figure 1 As shown. Figure 1It can be seen that new infrared characteristic peaks that do not exist in the original polymer are generated, namely the NH peak, Si-O-Li peak and Si-O-Al peak, which clearly indicates the generation of the key characteristic peaks of the hydrogel promoter.
[0042] From the above analysis, it can be seen that the structure of the hydrogel promoter is shown in formula (1):
[0043]
[0044] 2. Preparation of high-interfacial-activity in-situ self-assembled tough cement-based pavement materials
[0045] (S1) Preparation of hydrogel initiating solution: 2.5 parts by weight of poly (N-isopropylacrylamide) (NIPAm), 0.75 parts by weight of sodium acrylate (SA), 0.075 parts by weight of N,N-methylenebisacrylamide, 0.075 parts by weight of potassium persulfate, and 40 parts by weight of water are taken. The above components are mixed and stirred evenly to obtain a hydrogel initiating solution for later use.
[0046] (S2) Take the following raw materials in the following proportions: 45 parts by weight of 42.5 ordinary Portland cement, 0.3 parts by weight of the hydrogel accelerator (TL) prepared in step 1 of this embodiment, and 45 parts by weight of the hydrogel initiating solution prepared in step (S1).
[0047] (S3) Add the 42.5% ordinary Portland cement and the hydrogel initiating solution in step (S2) to the hydrogel accelerator (TL), and then stir continuously at a speed of 1200 r / min for 3 minutes to obtain a cement-based pavement material. Then, let it stand for 10 minutes, and test various properties of the pavement material after it solidifies and hardens.
[0048] Among them: the elongation at break is measured according to the standard of GB / T 23445-2009 "Polymer Cement Waterproof Coating", the bonding strength is measured according to the standard of JC / T 2381-2016 "Repair Mortar", the impact absorption is measured according to the standard of GB 36246-2018 "Synthetic Material Surface Sports Field for Primary and Secondary School Students", and the tensile strength retention rate after 240 hours of ultraviolet treatment is measured according to the standard of GB / T23445-2009 "Polymer Cement Waterproof Coating". The test results of the above indicators are shown in Table 1 below.
[0049] Table 1 Performance results of pavement materials in Example 1
[0050] Test indicators Elongation at break / % Bond strength / MPa Shock absorption / % Tensile strength retention rate / % Test Results 72.3 1.76 49.8 98.2
[0051] As can be seen from Table 1, under the premise that the impact absorption fully meets the standard requirements, the aging resistance is greatly improved, the tensile strength retention rate after 240 hours of ultraviolet treatment reaches 98.2%, and the bonding strength exceeds the maximum value (1MPa) required by the standard by 76%, indicating that this material has excellent performance. In addition, this material is an organic-inorganic composite material, which is green, environmentally friendly, non-toxic and harmless. Compared with the flexible walkway materials on the market, the comprehensive cost of construction, materials and maintenance is reduced by more than 200%.
[0052] in addition, Figure 2 This is a sample image of the pavement material prepared in this embodiment after solidification and hardening. Figure 2 It can be seen that it has excellent flexibility.
[0053] Figure 3 This is a scanning electron microscope (SEM) image of the road surface material prepared in this embodiment. Figure 3 It can be seen that the interface between the cement matrix and the hydrogel contains a large amount of high-strength cement hydration products CSH gel and ettringite (Aft), which makes the interface between the two have good bonding strength.
[0054] Example 2
[0055] 1. Preparation of hydrogel accelerator
[0056] (1) tetramethylenediamine is completely placed in a 0.25 mol / L sodium hydroxide solution for surface treatment for 12 hours. After completion, the system is adjusted to neutrality with 0.1 mol / L nitric acid, and then a 3% by mass silane coupling agent (KH-570) aqueous solution is added according to a mass ratio of tetramethylenediamine to silane coupling agent of 0.15:0.06, and then heated to 80°C and continuously stirred at a speed of 200 r / min for 0.5 hours at this temperature. After completion, a system containing an intermediate (TK) is obtained and is set aside;
[0057] (2) Adding lithium aluminosilicate (LiAlSiO 4 ), the mass ratio of the two is 0.3:0.2. Then it is heated to 50°C and stirred continuously at 500r / min for 5.5h at this temperature, and the hydrogel promoter (TL) is obtained after completion.
[0058] 2. Preparation of high-interfacial-activity in-situ self-assembled tough cement-based pavement materials
[0059] (S1) Preparation of hydrogel initiating solution: 1 part by weight of poly (N-isopropylacrylamide) (NIPAm), 0.3 parts by weight of sodium acrylate (SA), 0.03 parts by weight of N,N-methylenebisacrylamide, 0.03 parts by weight of sodium persulfate, and 20 parts by weight of water. Mix the above components and stir evenly to obtain a hydrogel initiating solution for later use.
[0060] (S2) Take the following raw materials in the following proportions: 20 parts by weight of 42.5 ordinary Portland cement, 0.2 parts by weight of the hydrogel accelerator (TL) prepared in step 1 of this embodiment, and 20 parts by weight of the hydrogel initiating solution prepared in step (S1).
[0061] (S3) Add the 42.5 ordinary Portland cement and the hydrogel initiating solution in step (S2) to the hydrogel accelerator (TL), and then stir continuously at a speed of 1200 r / min for 3 minutes to obtain a cement-based pavement material. Then, let it stand for 10 minutes, and after the pavement material solidifies and hardens, test its various properties. The test method is the same as that of the above-mentioned Example 1, and the results are shown in Table 2 below.
[0062] Table 2 Performance results of pavement materials in Example 2
[0063]
[0064] Example 3
[0065] 1. Preparation of hydrogel accelerator
[0066] (1) The tetramethylenediamine was completely placed in a 0.03 mol / L sodium hydroxide solution for surface treatment for 8 hours. After completion, the system was adjusted to neutrality with 0.1 mol / L sulfuric acid. Then, a 3% mass fraction of a silane coupling agent (KH-570) aqueous solution was added according to a mass ratio of the tetramethylenediamine to the silane coupling agent of 0.1:0.08. Then, the mixture was heated to 40°C and stirred continuously at a speed of 200 r / min for 3.5 hours at the same temperature. After completion, a system containing the intermediate (TK) was obtained and set aside.
[0067] (2) Adding lithium aluminosilicate (LiAlSiO 4 ), the mass ratio of the two is 0.1:0.08. Then, it is heated to 95°C and stirred continuously at 500r / min for 1.5h at this temperature, and the hydrogel promoter (TL) is obtained after completion.
[0068] 2. Preparation of high-interfacial-activity in-situ self-assembled tough cement-based pavement materials
[0069] (S1) Preparation of hydrogel initiating solution: 5 parts by weight of poly N-isopropylacrylamide (NIPAm), 1.5 parts by weight of sodium acrylate (SA), 0.12 parts by weight of N,N'-methylenebisacrylamide, 0.12 parts by weight of ammonium persulfate, and 60 parts by weight of water. Mix the above components and stir evenly to obtain a hydrogel initiating solution for later use.
[0070] (S2) Take the following raw materials in the following proportions: 60 parts by weight of 42.5 ordinary Portland cement, 0.5 parts by weight of the hydrogel accelerator (TL) prepared in step 1 of this embodiment, and 60 parts by weight of the hydrogel initiating solution prepared in step (S1).
[0071] (S3) Add the 42.5 ordinary Portland cement and the hydrogel initiating solution in step (S2) to the hydrogel accelerator (TL), and then stir continuously at a speed of 1200 r / min for 3 minutes to obtain a cement-based pavement material. Then, let it stand for 10 minutes, and after the pavement material solidifies and hardens, test its various properties. The test method is the same as that of the above-mentioned Example 1, and the results are shown in Table 3 below.
[0072] Table 3 Performance results of road surface materials in Example 3
[0073]
[0074] Comparative Example 1
[0075] The preparation process is the same as that of Example 1, except that step (2) of step 1 is omitted, and the system with the intermediate (TK) prepared in Example 1 is used instead of the finally obtained hydrogel accelerator to directly prepare the cement-based pavement material, as follows:
[0076] (S1) Take the following raw materials: 45 parts by weight of 42.5 ordinary Portland cement, 0.3 parts by weight of the system containing the intermediate (TK) prepared in step 1 of the above embodiment 1, and 45 parts by weight of the hydrogel initiating solution prepared in the above embodiment 1.
[0077] (S2) Add the 42.5 ordinary Portland cement and hydrogel initiator solution of step (S1) to the system containing the intermediate (TK), and then stir continuously at a speed of 1200r / min for 3min, i.e., the cement-based pavement material. Then, let it stand for 10min, and after the pavement material solidifies and hardens, test its various properties. The test method is the same as that of the above-mentioned Example 1, and the results are shown in Table 4 below.
[0078] Table 4 Comparative Example 1 Pavement Material Performance Results
[0079]
[0080] Comparative Example 2
[0081] The preparation process is the same as that of Example 2, except that step (2) of step 1 is omitted, and the system containing the intermediate (TK) prepared in Example 2 and lithium aluminosilicate are directly added as raw materials instead of the hydrogel accelerator to prepare the cement-based pavement material, specifically as follows: (S1) Take the following raw materials in the following proportions: 20 parts by weight of 42.5 ordinary Portland cement, 0.12 parts by weight of the system containing the intermediate (TK) prepared in step 1 of the above Example 2, and lithium aluminosilicate (LiAlSiO 4 ) 0.08 weight parts, and 20 weight parts of the hydrogel initiating solution prepared in the above embodiment 2.
[0082] (S2) Adding the 42.5 ordinary Portland cement and the hydrogel initiating solution in step (S1) to the system containing the intermediate (TK), then adding the lithium aluminosilicate, and then continuously stirring at a speed of 1200 r / min for 3 minutes to obtain a cement-based pavement material. Then standing for 10 minutes, after the pavement material solidifies and hardens, its various properties are tested, the testing method is the same as the above-mentioned Example 1, and the results are shown in the following Table 5.
[0083] Table 5 Comparative Example 2 Road Surface Material Performance Results
[0084]
[0085] Comparative Example 3
[0086] The preparation process is the same as that of Example 3, except that no silane coupling agent is used, and the hydrogel accelerator is directly prepared, as follows:
[0087] 1. Preparation of hydrogel accelerator
[0088] (1) The tetramethylenediamine is completely placed in a 0.03 mol / L sodium hydroxide solution for surface treatment. After completion, the system is adjusted to neutrality with 0.1 mol / L sulfuric acid, and then heated to 40°C and stirred continuously at 200 r / min for 3.5 hours at this temperature. After completion, a system containing an intermediate is obtained and is ready for use.
[0089] (2) Adding lithium aluminosilicate (LiAlSiO 4 ), the mass ratio of the two is 0.1:0.08. Then, it is heated to 95°C and stirred continuously at 500r / min for 1.5h at this temperature, and the hydrogel accelerator is obtained after completion.
[0090] (S3) Add the 42.5 ordinary Portland cement and the hydrogel initiating solution in step (S2) to the hydrogel accelerator (TL), and then stir continuously at a speed of 1200 r / min for 3 minutes to obtain a cement-based pavement material. Then, let it stand for 10 minutes, and after the pavement material solidifies and hardens, test its various properties. The test method is the same as that of the above-mentioned Example 1, and the results are shown in Table 6 below.
[0091] 2. Preparation of cement-based pavement materials
[0092] (S1) Preparation of hydrogel initiating solution: 5 parts by weight of poly N-isopropylacrylamide (NIPAm), 1.5 parts by weight of sodium acrylate (SA), 0.12 parts by weight of N,N'-methylenebisacrylamide, 0.12 parts by weight of ammonium persulfate, and 60 parts by weight of water. Mix the above components and stir evenly to obtain a hydrogel initiating solution for later use.
[0093] (S2) Take the following raw materials in the following proportions: 60 parts by weight of 42.5 ordinary Portland cement, 0.5 parts by weight of the hydrogel accelerator prepared in step 1 of this embodiment, and 60 parts by weight of the hydrogel initiating solution prepared in step (S1).
[0094] (S3) Add the 42.5 ordinary Portland cement and the hydrogel initiating solution in step (S2) to the hydrogel accelerator, and then stir continuously at a speed of 1200 r / min for 3 minutes to obtain a cement-based pavement material. Then, let it stand for 10 minutes, and after the pavement material solidifies and hardens, test its various properties. The test method is the same as that of the above-mentioned Example 1, and the results are shown in Table 6 below.
[0095] Table 6 Comparative Example 3 Road Surface Material Performance Results
[0096]
[0097] Comparative Example 4
[0098] The preparation of cement-based pavement material is the same as in Example 2, except that no hydrogel accelerator is prepared, and lithium aluminosilicate is directly used instead of the hydrogel accelerator to prepare the cement-based pavement material, as follows:
[0099] (S1) Preparation of hydrogel initiating solution: 1 part by weight of poly (N-isopropylacrylamide) (NIPAm), 0.3 parts by weight of sodium acrylate (SA), 0.03 parts by weight of N,N-methylenebisacrylamide, 0.03 parts by weight of sodium persulfate, and 20 parts by weight of water. Mix the above components and stir evenly to obtain a hydrogel initiating solution for later use.
[0100] (S2) Take the following raw materials in the following proportions: 42.5 parts by weight of ordinary Portland cement, 20 parts by weight of lithium aluminosilicate (LiAlSiO 4) 0.2 weight parts, and 20 weight parts of the hydrogel initiating solution prepared in this example.
[0101] (S3) The 42.5 ordinary Portland cement and the hydrogel initiating solution in step (S2) are mixed with lithium aluminosilicate, and then stirred continuously at a speed of 1200 r / min for 3 minutes to obtain a cement-based pavement material. Then, the pavement material is allowed to stand for 10 minutes, and various properties thereof are tested after solidification and hardening. The testing method is the same as that in the above-mentioned embodiment 1, and the results are shown in the following Table 7.
[0102] Table 7 Comparative Example 4 Road Surface Material Performance Results
[0103]
[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high interfacial activity in-situ self-assembled tough cement-based pavement material, characterized in that: The pavement material comprises the following raw materials in parts by weight: 20 to 60 parts of a cementitious material containing silicate cement, 0.2 to 0.5 parts of a hydrogel accelerator, and 1 to 7 parts of a hydrogel initiating solution, wherein the hydrogel initiating solution comprises 1 to 5 parts of poly (N-isopropylacrylamide), 0.3 to 1.5 parts of sodium acrylate, 0.03 to 0.12 parts of a cross-linking agent, 0.03 to 0.12 parts of an initiator, and 20 to 60 parts of water; the chemical structural formula of the hydrogel accelerator is shown in formula (1):
2. The high interfacial activity in-situ self-assembled tough cement-based pavement material according to claim 1, characterized in that: The preparation method of the hydrogel accelerator comprises the following steps: (1) placing tetramethylenediamine in an alkali solution for surface treatment, adjusting to neutrality, adding a silane coupling agent, and heating for reaction to obtain a system containing an intermediate; (2) Adding lithium aluminosilicate to the system containing the intermediate obtained in step (1), heating the system for reaction, and obtaining a hydrogel accelerator.
3. The high interfacial activity in-situ self-assembled tough cement-based pavement material according to claim 2, characterized in that: In step (1), the alkali solution includes at least one of a sodium hydroxide solution and a potassium hydroxide solution, and the concentration of the alkali solution is 0.03 to 0.25 mol / L.
4. The high interfacial activity in-situ self-assembled tough cement-based pavement material according to claim 2, characterized in that: In step (1), an acidic substance is used to adjust the solution to neutrality, and the acidic substance includes at least one of nitric acid and sulfuric acid.
5. The in-situ self-assembled tough cement-based pavement material with high interfacial activity according to claim 2, characterized in that: In step (1), the silane coupling agent includes γ-methacryloxypropyltrimethoxysilane, the mass ratio of tetramethylenediamine to silane coupling agent is 0.1-0.3:0.03-0.08, the heating reaction temperature is 40-80°C, and the heating reaction time is 0.5-3.5h.
6. The in-situ self-assembled tough cement-based pavement material with high interfacial activity according to claim 2, characterized in that: In step (1), continuous stirring is performed during the reaction.
7. The in-situ self-assembled tough cement-based pavement material with high interfacial activity according to claim 2, characterized in that: In step (2), the mass ratio of tetramethylenediamine to lithium aluminosilicate is 0.1-0.3:0.08-0.2, the heating reaction temperature is 50-95° C., and the heating reaction time is 1.5-5.5 h.
8. The in-situ self-assembled tough cement-based pavement material with high interfacial activity according to claim 2, characterized in that: In step (2), continuous stirring is performed during the reaction.
9. The high interfacial activity in-situ self-assembled tough cement-based pavement material according to claim 1, characterized in that: The initiator includes at least one of potassium persulfate, ammonium persulfate and sodium persulfate, and the cross-linking agent includes at least one of N,N-methylenebisacrylamide and N,N'-methylenebisacrylamide.
10. The method for preparing the in-situ self-assembled tough cement-based pavement material with high interfacial activity according to any one of claims 1 to 9, characterized in that: The following steps are involved: Add the cementitious material containing silicate cement and the hydrogel initiating solution into the hydrogel accelerator and mix them evenly to obtain the hydrogel.
Citation Information
Patent Citations
Hydrogel biocement systems and method
WO2017139750A1